2016
DOI: 10.1039/c5gc02164b
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid zeolites for tandem Diels–Alder cycloaddition and dehydration of biomass-derived dimethylfuran and ethylene to renewable p-xylene

Abstract: p-Xylene was synthesized by [4 + 2] cycloaddition of biomass-derived ethylene and dimethylfuran over Lewis acid zeolite catalyst, Zr-BEA, with 90% selectivity in products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
166
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(174 citation statements)
references
References 31 publications
6
166
2
Order By: Relevance
“…In addition to CI, other side products, i.e., AT, AC, and OLI, also formed in considerable amounts. Overall, Zr-Beta showed superior performance to Sn-Beta for the Diels-Alder reaction, which is in accordance with findings in the literature [25,26]; however, its activity was still poorer than that of Na-Y zeolite. Na-Y showed a lower conversion of MF (55%) than Zr-Beta, but the toluene selectivity (69%) was much higher than that of Zr-Beta (18%).…”
Section: Effect Of Other Lewis Acid Zeolitessupporting
confidence: 91%
See 2 more Smart Citations
“…In addition to CI, other side products, i.e., AT, AC, and OLI, also formed in considerable amounts. Overall, Zr-Beta showed superior performance to Sn-Beta for the Diels-Alder reaction, which is in accordance with findings in the literature [25,26]; however, its activity was still poorer than that of Na-Y zeolite. Na-Y showed a lower conversion of MF (55%) than Zr-Beta, but the toluene selectivity (69%) was much higher than that of Zr-Beta (18%).…”
Section: Effect Of Other Lewis Acid Zeolitessupporting
confidence: 91%
“…Specifically, Sn-and Zr-Beta zeolites have Lewis acid sites, which originate from tetrahedrally coordinated framework metal centers, unlike cationexchanged Y zeolites. It was recently shown that Sn-and Zr-Beta are fairly active for the Diels-Alder reaction of DMF and ethylene as well as for the Diels-Alder reaction of oxidized derivatives of DMF and ethylene [17,25,26]. Thus, these Lewis acid zeolites were also investigated for the reaction of MF and ethylene.…”
Section: Effect Of Other Lewis Acid Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of terephthalic acid (TPA), the common approach targets renewable p-xylene as a drop-in for oxidation in the AMOCO process (Scheme 1a). [10][11][12] However, oxidation-free routes through muconic acid (MA), a platform intermediate from sugar and lignin fermentation, [13][14][15][16][17][18][19] have also emerged (Scheme 1b). The MA route can be considered advantageous as this intermediate can be converted to a variety of commodity and specialty chemicals, including adipic acid, 14,19,20 TPA, 4,5,21 and 1,4-cyclohexanedicarboxylic acid (CHDA).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Selectivep roduction of p-xylene from dimethylfuran and ethylene with zeoliteB etac atalyst was developed by Chang et al [14] Here, we used similar chemistry to prepare precursors to p-methylstyrene and p-divinylbenzene. [6][7][8][9][10][11][12][13] Selectivep roduction of p-xylene from dimethylfuran and ethylene with zeoliteB etac atalyst was developed by Chang et al [14] Here, we used similar chemistry to prepare precursors to p-methylstyrene and p-divinylbenzene.…”
Section: Introductionmentioning
confidence: 99%